A comprehensive review on the adsorptive removal of pharmaceutical pollutants: Occurrence, toxicology, molecular simulation and mechanistic insights - Mochamad Lutfi Firmansyah; Yousef Alwan; Nisar Ullah (Talanta Open)
Amid rapid industrialization and soaring population growth, there is an ever-increasing global use of medicines that has grown by 14 % over the past five years. The excessive use of pharmaceuticals causes contamination of water bodies through domestic and hospital effluents, as well as by pharmaceutical companies. This in turn threatens global drinking water supplies. Moreover, the biologically active nature of pharmaceutical pollutants (PPs) makes it difficult to degrade in wastewater and hence poses notable risks to both public health and as well as the environment. Given the growing interest in the removal of PPs from wastewater, adsorption is regarded as a simple yet highly effective strategy. In this review, we catalogue recent progress in the adsorptive removal of PPs from wastewater, covering the period from 2013 to the present date. We have systematically covered the comparative overview of existing removal approaches, followed by a detailed examination of various adsorbent materials. Moreover, the influence of porosity, surface area, and functional groups on the adsorption efficiency has been discussed. Likewise, critical considerations, such as optimizing maximum adsorption capacity, the effect of pH, adsorption mechanisms, and adsorbent regeneration, have been analyzed. Moreover, computational and machine-learning–guided molecular design methods in the design of the adsorbent has also been reviewed. Furthermore, the toxicity and hazardous effects of PPs on human health, aquatic ecosystems, and the environment have been extensively discussed. Finally, we outline the disadvantages of the existing adsorbents, elaboration on the research gaps and possible solutions, with the aim to develop more efficient and cost-effective adsorbents in the quest to remove PPs from wastewater.